Assessment of the Distributive Impact of National and External Trade Reforms in Brazil - Fernando Borraz; Máximo Rossi; Daniel Ferres (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
This paper quantifies the distributional and poverty effects of national and external trade reform in Brazil using household survey data. We estimate the consumption and labor impact of the Mercosur trade reform following the methodology suggested by Porto (2006). In order to analyze the impact of external trade reforms over the Brazilian economy, we focus a major exported good: broiler. Results show that trade liberalization benefits more low income individuals. This result is largely explained by two major observations: the fact that consumption good prices decreased as Brazil enter Mercosur and a close to zero labor income effect. Additionally, we find that poverty indicators decreased after national trade liberalization (both for women and men). We obtained no significant inequality effects after national trade reforms. We analyze the impact on poverty and inequality of a 10% increase the broiler world price. In general terms, we find an increase in poverty of two points and no effect on income inequality.
Keywords: F14; F16; D30; Q17; 330; internal and external trade reform; poverty; inequality